Foundations of finance the logic and practice of financial management - Keown, Arthur J.; Martin, John D.; Petty, J. William (Pearson, 2017)
As in previous editions, the Ninth Edition focuses on valuation and opens every chapter with a vignette based on financial decisions faced by contemporary, real-world companies and firms. Revised and updated, the newest edition includes new lecture videos, financial thinking, user feedback, and lessons from the recent economic crisis.